2013
DOI: 10.2147/idr.s44724
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria among elderly and middle-aged rural community-dwellers in South-Western Nigeria

Abstract: Asymptomatic bacteriuria in elderly individuals has been well described in institutionalized settings, but to a lesser extent in the community. The purpose of this study was to determine the pathogens responsible for asymptomatic bacteriuria in elderly and middle-aged individuals in Alajue-Ede, South-Western Nigeria, and to identify any associated factors. Mid-stream urine samples were collected from apparently healthy elderly and middle-aged volunteers who were participating in community health screening. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…The high prevalence among the subjects might be due to contaminants from procedural error or perennial skin. However, significantly higher level of bacteriuria observed among the females is in agreement with the findings of several earlier studies[ 6 14 15 20 ] and it might be related to the short course of the female urethra and its proximity to the anorectal region. [ 21 22 ]…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The high prevalence among the subjects might be due to contaminants from procedural error or perennial skin. However, significantly higher level of bacteriuria observed among the females is in agreement with the findings of several earlier studies[ 6 14 15 20 ] and it might be related to the short course of the female urethra and its proximity to the anorectal region. [ 21 22 ]…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in contrast to several reports, which identified E. coli as the most common uropathogen causing asymptomatic bacteriuria. [ 15 23 24 ] However, this study aligns with the findings of Dada-Adegbola and Muili[ 25 ] who reported K. pneumoniae as the leading urinary pathogen. Furthermore, the increasing isolation of S. aureus as one of the major causes of UTI has also been reported, thereby suggesting the importance of these bacteria in UTIs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations